QUALITY OF SERVICE BASED WEB SERVICE SELECTION: AN EVALUATION OF TECHNIQUES - Rigga Widar Atmagi; Munjiah Nur Saadah (JUTI: Jurnal Ilmiah Teknologi Informasi, 2012)
In service oriented computing, web services are the basic construct that aims to facilitate building of business application in a more flexible and interoperable manner for enterprise collaboration. One of the most promising advantages of web service technology is the possibility of creating added-value services by combining existing ones. A key step for composing and executing services lies in the selection of the individual services to use. Much attention has been devoted to appropriate selection of service functionalities, but also the non-functional properties of the services play a key role. A web service selection technique must take as much as possible the important influencing aspects into account to the selection processes in order to minimize the selection efforts. This paper evaluates several web service selection techniques published in literature with the focus on their contributions to web service selection. The evaluation results may be used as a basis for improving web service selection techniques that may simplify the selection tasks.